Congruency of Information Rather Than Body Ownership Enhances Motor Performance in Highly Embodied Virtual Reality - Odermatt, Ingrid A.; Buetler, Karin A.; Wenk, Nicolas; Özen, Özhan; Penalver-Andres, Joaquin; Nef, Tobias; Mast, Fred W.; Marchal-Crespo, Laura (Frontiers in Neuroscience, 2021)
In immersive virtual reality, the own body is often visually represented by an avatar. This may induce a feeling of body ownership over the virtual limbs. Importantly, body ownership and the motor system share neural correlates. Yet, evidence on the functionality of this anatomical coupling is still inconclusive. Findings from previous studies may be confounded by the congruent vs incongruent multisensory stimulation used to modulate body ownership. This study aimed to investigate the effect of body ownership and congruency of information on motor performance in immersive virtual reality. We aimed to modulate body ownership by providing congruent vs incongruent visuo-tactile stimulation (i.e., participants felt a brush stroking their real fingers while seeing a virtual brush stroking the same vs different virtual fingers). To control for congruency effects, unimodal stimulation conditions (i.e., only visual or tactile) with hypothesized low body ownership were included. Fifty healthy participants performed a decision-making (pressing a button as fast as possible) and a motor task (following a defined path). Body ownership was assessed subjectively with established questionnaires and objectively with galvanic skin response (GSR) when exposed to a threat. Our results suggest that congruency of information may facilitate reaction times and completion time of motor tasks in immersive virtual reality. Moreover, subjective body ownership is associated with faster reaction times, whereas its benefit on motor task performance needs further investigation. Therefore, it might be beneficial to provide congruent information in immersive virtual environments, especially during the training of motor tasks, e.g., in neurorehabilitation interventions.